What works in development? thinking big and thinking small - Cohen, Jessica (Washington, D.C Brookings Institution Press, 2009)
What Works in Development? brings together leading experts to address one of the most basic yet vexing issues in development: what do we really know about what works ? and what doesn't ?in fighting global poverty?
Includes bibliographical references and index.
Keywords: Economic development